Exploring First-Person Perspectives in Designing a Role-Playing VR Simulation for Bullying Prevention: A Focus Group Study - Oyekoya, Oyewole; Urbanski, Jan; Shynkar, Yaroslava; Baksh, Arifa; Oyekoya, Margaret (Frontiers in Virtual Reality, 2021)
Bullying is a complex and abusive form of violence that has potentially serious social and mental health consequences for children and adolescents. With reference to the Olweus Bullying Circle, this project involves the development of a simulation that will allow students to view themselves in different roles played in bullying situations using a virtual reality setting. Interventions need to explore the perspective of the student who bullies and the student being bullied, as well as the bystander in order to model desirable intervention behavior. The expectation is that through role-playing, the students will explore different perspectives and learn how to respond to bullying situations. Two focus groups were conducted to allow experts to contribute to the design of the bullying prevention simulation and gather suggestions for improvements. Findings from the focus group studies suggest that to create effective bullying prevention, VR simulations should consider focusing on role-playing, customization of the characters, environments, scenarios and a scoring/reward system.